Coriolis mass flow metering for wet gas - Lansangan, R; Skinner, J; Reese, M; Del Toro, A; Tombs, M; Duta, M; Zhou, F; Henry, M (SAGE Publications, 2008)
Most two-phase applications for Coriolis mass flow metering are for low Gas Void Fraction (GVF) conditions, i.e. where the process fluid is essentially liquid with relatively low levels of entrained air or gas. There are particular challenges associated with metering wet gas, where the GVF exceeds 95%. Established wet gas metering techniques are typically based on a differential pressure-type device (for example an orifice plate or V-cone). It is well-known that such devices over-read compared to a dry gas calibration; equations to correct the reading are available if the degree of gas "wetness" is known. For Coriolis mass flow metering of wet gas, two approaches are described. The natural extension of the low GVF techniques is to map the observed mass flow and density readings onto estimates of the flow rates of the gas and liquid components. The alternative is to use the Coriolis meter to estimate the degree of gas "wetness" (e.g. the Lockhart-Martinelli number) and to apply a conventional correlation (e.g. Murdock or Chisholm) to a differential pressure flow reading. A prototype Coriolis-based wet gas meter is described, together with results from laboratory trials at CEESI in Colorado, and from extended field trials at BP's Wamsutter gas field in Wyoming.